Mahasiswa Teologi Sebagai Agen Perubahan:Upaya Mewujudkan Keesaan Gereja di Era Modern - Lela Siska Indriani Samosir; Meditatio Situmorang (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This article is titled "The Role of Theology Students as Agents of Change in Realizing Church Unity in the Modern Era." Church unity is a fundamental principle in Christianity that emphasizes the importance of collaboration among denominations. In today's increasingly pluralistic society, divisions and conflicting theological perspectives pose significant challenges to constructive dialogue and cooperation among churches. Therefore, theology students have a significant role in advocating for unity through the Ecumenical movement. Using qualitative research methods that focus on library data collection, this article explores how theology students can contribute to fostering dialogue, initiating social service projects, and utilizing social media to promote messages of unity. Their active involvement in these efforts is expected to bridge gaps, reduce stereotypes, and enhance collaboration among churches. Through these initiatives, theology students not only gain a deeper understanding of church unity but also become transformative agents who embody the values ​​of love and cooperation. As a result, the church can emerge as a more united witness in the world, reflecting the inclusive love of Christ.